1995
DOI: 10.1163/003925995x00206
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Nematode-Trapping Fungi Following Their Encapsulation in Alginate

Abstract: Granular formulations of Dactylella candida and Arthrobotrys dactyloides were prepared by encapsulating different quantities of fungal biomass in alginate, or by subjecting encapsulated biomass to further fermentation. Results of experiments with these formulations showed that the presence of nutrients and the quality and quantity of biomass in granules determined their level of activity against nematodes. The best formulations were those in which granules were fermented after the fungus had been encapsulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(Persson et al, 1993) state that isolates of nematophagous fungi like Arthrobotrys dactyloides and A. superba have the ability to colonize tomato roots resulting in an effective biological control. Previous studies (Stirling and Mani, 1995;Galper et al, 1995;Jaffee and Muldoon, 1997;Jacobs, 1997;Stirling et al, 1998) reported the ability of Arthrobotrys to suppress Meloidogyne spp. The results obtained agree with jobs where Meloidogyne is associated with beneficial soil microorganisms (Gallegos et al, 2009).…”
Section: Agradecimientosmentioning
confidence: 99%
“…(Persson et al, 1993) state that isolates of nematophagous fungi like Arthrobotrys dactyloides and A. superba have the ability to colonize tomato roots resulting in an effective biological control. Previous studies (Stirling and Mani, 1995;Galper et al, 1995;Jaffee and Muldoon, 1997;Jacobs, 1997;Stirling et al, 1998) reported the ability of Arthrobotrys to suppress Meloidogyne spp. The results obtained agree with jobs where Meloidogyne is associated with beneficial soil microorganisms (Gallegos et al, 2009).…”
Section: Agradecimientosmentioning
confidence: 99%
“…Linford (Linford, 1937) Linford, 1937;Linford , 1938 (Kim , 1997). (Cayrol, 1983;Stirling Mani, 1995) (Cayrol, 1983;Pelagatti and Piccolo, 1990). , ,…”
mentioning
confidence: 99%
“…fungistasis (Cooke Satchuthananthavale, 1968;Dobbs Hinson, 1953;Mankau, 1962), (Galper , 1995), (Hastuti Faull, 2018;Stirling Mani, 1995), (Gaspard Mankau, 1987;Rosenzweig , 1985) . (Rosenzweig , 1985).…”
mentioning
confidence: 99%